Penerapan Model Cooperative Script dengan Menggunakan Media Audiovisual Tiktok dalam Pembelajaran Menulis Puisi Kelas VIII SMPN 5 Kota Jambi - Maulana, Resky; Rasdawita, Rasdawita; Ningsih, Arum Gati (Jurnal Ilmiah Dikdaya, 2024)
This study aims to describe the application of the cooperative script model with audiovisual media tiktok in learning towrite poetry texts of class VIII A students of SMPN 5 Jambi City located in Jelutung District, Jambi City. the research methodused is qualitative through a descriptive approach. The type of research used is a case study to see the application using 4 stagesscientifically: 1) Observation, 2) Interview, 3) Test, 4) Document Analysis. The documentation of this study shows the results ofthe application of the cooperative script model in learning to write poetry. The description of this research is guided by theteacher's teaching module and the implementation instrument of the cooperative script model. The research subjects werestudents of class VIII A, and the research object was writing poetry text. The data collection techniques were tests, interviews, andobservations. The aspects assessed were the students' ability to write poetry based on the theme, keywords, imagery, languagestyle, and diction. The results of his research show that learning to write poetry with the cooperative script model and assisted bytiktok audiovisual media in learning to write poetry in Indonesian language learning independent curriculum in class VIII ASMPN 5 Jambi City is implemented to help students write poetry well according to the steps and has obtained good results. Thedetails of the scores are seen from the existence of poems 1 and 2, out of 15 groups, there were 11 and 13 groups that got goodscores, and 4 and 2 groups got quite good scores. For individual scores, 27 out of 31 learners scored very well, and 4 out of 31learners scored wel